Comparison of productive parameters of two guinea pig meat lines in the central coast of Peru - Yamada A., Graciela (2019)
The aim of this study was to compare the productive performance of two guinea pig meat lines (Cavia porcellus) reared in the central coast of Peru. Two genetic lines of guinea pigs were used during the growth and fattening stage: a group of 20 male guinea pig, progeny of improved guinea pigs in the Peruvian highlands, meat line G, and another group of 20 improved male guinea pigs in the Peruvian coast, meat line H. The guinea pigs were reared in individual cages from weaning (15 ± 2 days) until week 11, receiving the same diet based on Zea mays var. indurata, wheat bran and fresh water. The birth weight for guinea pigs G and H was 146.5 ± 28.2 and 119.0 ± 19.2 g, respectively, the weaning weight was 306.5 ± 49.1 and 227.0 ± 58.2, respectively, and the weight at week 11 was 965.5 ± 100.2 and 868.0 ± 91.6, respectively (p<0.05 in all cases). No significant difference was found in daily weight gain per day, total weight gain, feed conversion ratio and carcass yield; however, guinea pigs of line H showed a higher daily feed consumption and total feed consumption, and lower carcass weight than guinea pigs of line G (p<0.05). It is concluded that the guinea pigs have a greater body weight at age of slaughter (week 11), as well as a greater carcass weight and better economic retribution than the guinea pigs H.